1997
DOI: 10.1021/la950940a
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Study of Adsorption from Mixtures of Dimers and Monomers on Heterogeneous Solid Surfaces

Abstract: The results of a Monte Carlo simulation for adsorption from solutions of monomers and dimers on heterogeneous surfaces are presented. The adsorption and orientation of dimers adsorbed on surfaces of different (striplike and chessboard) topography are discussed. It is demonstrated that the surface topography has a considerable effect on the adsorption and orientation of dimers only when the size of the homotatic domains is smaller than the length of the adsorbed rodlike molecules. For larger patches, the adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…On the other hand, only a few researchers have endeavored to explore the effect of surface geometric heterogeneity on gas adsorption via molecular simulation, although atomistic modeling provides a feasible microscopic approach to describing pore surfaces more realistically . Most of their studies have shown that the surface geometric heterogeneity can notably affect gas adsorption. ,,,,, Bojan and Steele, for example, compared the adsorption of krypton on a steplike graphitic surface with that on a flat graphitic surface by molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, only a few researchers have endeavored to explore the effect of surface geometric heterogeneity on gas adsorption via molecular simulation, although atomistic modeling provides a feasible microscopic approach to describing pore surfaces more realistically . Most of their studies have shown that the surface geometric heterogeneity can notably affect gas adsorption. ,,,,, Bojan and Steele, for example, compared the adsorption of krypton on a steplike graphitic surface with that on a flat graphitic surface by molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the characteristic width of the corrugations (λ), the models can be classified into two categories . (1) λ ≫ Atomic scale: typical appearances of this category include defective surfaces, , sinusoidal surfaces, and homotattic surface patches ,,,, introduced by Langmuir (e.g., steplike surfaces ,, and chessboard-like pillared surfaces ,, ). (2) λ ∼ Atomic scale: proposed by Hill, random heterogeneity represents a notable feature of this category (see refs , , , , , , , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation is an efficient method for resolving the above mentioned problems, since it is capable of modelling the processes of interest at the required level of detail in a controllable environment, providing the necessary tools for establishing the connections between the observed phenomena and their molecular-level physical background. Prof. Sokołowski's (and co-workers) research topics of interest have also been concerned with the issue of mixtures using Monte Carlo simulations [15][16][17][18][19][20][21][22], Density Functional Theory [23][24][25][26][27][28], and Dissipative Particle Dynamics [29]. Their inspiring articles discuss, for example, the following problems: (i) adsorption from mixtures of monomers [15], dimers [15], the chain molecules [30,31], and even polymer mixtures [27], (ii) adsorption from mixtures on homogeneous [25,32] and heterogeneous surfaces [15,33,34], (iii) layering transition, capillary condensation, wetting phenomena, and multilayer adsorption of binary ideal mixtures, systems exhibiting negative deviations from ideal mixing or positive one, binary mixture with partially miscible components, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Prof. Sokołowski's (and co-workers) research topics of interest have also been concerned with the issue of mixtures using Monte Carlo simulations [15][16][17][18][19][20][21][22], Density Functional Theory [23][24][25][26][27][28], and Dissipative Particle Dynamics [29]. Their inspiring articles discuss, for example, the following problems: (i) adsorption from mixtures of monomers [15], dimers [15], the chain molecules [30,31], and even polymer mixtures [27], (ii) adsorption from mixtures on homogeneous [25,32] and heterogeneous surfaces [15,33,34], (iii) layering transition, capillary condensation, wetting phenomena, and multilayer adsorption of binary ideal mixtures, systems exhibiting negative deviations from ideal mixing or positive one, binary mixture with partially miscible components, etc. [16,17,[34][35][36][37][38], (iv) interaction of charged chain particles and spherical counterions in contact with charged hard wall [31], (v) analysis of the properties of two-dimensional symmetrical mixtures in an external field of square symmetry [39,40], (vi) demixing and freezing in two-dimensional symmetrical mixtures [21], and (vii) the behaviour of mixed two component submonolayer films (Ar and Kr [41,42] or Kr and Xe [22] on graphite).…”
Section: Introductionmentioning
confidence: 99%
“…The surface heterogeneity effects in the adsorption from the dimer-monomer and trimer-monomer solutions have been also studied in terms of the lattice model (30) and the Monte Carlo simulation (31,32). An influence of surface topography on the excess adsorption isotherms has been analyzed.…”
Section: Introductionmentioning
confidence: 99%